Nexus fundamental factors, systematic risk, and stock returns (the LQ45 Index for the 2020-2022 Period) - Widiastuti Widiastuti; Purwanti Purwanti (Faculty of Economics and Business Mulawarman University, 2023)
The primary objective of this research is to identify the impact of key drivers, such as profitability ratios such as Return on Assets (ROA), solvency ratios such as Debt to Equity Ratio (DER), market value ratios such as Price Earnings Ratio (PER), and systematic risk indicators such as Inflation and Reference Interest Rate. In contrast, Stock Return is the focus of this investigation. This study seeks to shed light on a mystery. Companies trading on the Indonesia Stock Exchange and included in the LQ45 Index from 2020 to 2022 comprise the study's population. Purposeful sampling was used, and 27 businesses were included in the sample. Descriptive multiple linear regression was employed in this work with panel data and Eviews 10. Using panel data, we find that (1) the ROA and PER ratios significantly affect LQ45 Index Stock Return, and (2) the DER ratio, inflation, and the Reference Interest Rate have little effect on LQ45 Index Stock Return.